The Cambridge history of Christianity / 1 Origins to Constantine / ed. by Margaret M. Mitchell ... - Mitchell, Margaret Mary (The Cambridge history of Christianity, 2006)
The political, social, and religious setting -- The Jesus movements -- Community traditions and self-definition -- The shaping of Christian theology -- "Aliens" become citizens : towards imperial patronage.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Hellenismus; Römisches Reich; Religion; Kirche; Frühchristentum; Theologie; Verbreitung; Gemeinschaftsgefühl; Gruppenidentität; Entwicklung; Geschichte 30-313; Gesellschaft; Politik; Christentum